John Savio’s Art as a Part of Early Sámi Decolonisation in the 1920s and 1930s - Hautala-Hirvioja, Tuija (Routledge, 2021)
John Savio (1902–1938) was born on the shore of Varangerfjord and spent his early years in Kirkenes in Finnmark. He visited this northernmost county in Norway several times, and he depicted its landscapes, Sámi culture and people. His own ancestors belonged to minorities; they were Kvens and Sámi. Savio was the first educated Sámi artist. This chapter examines how Savio used his Sámi-themed woodcuts as a tool for decolonisation in the 1920s and 1930s. They belong to the collection of Savio Museum in Kirkenes. In my analysis, Indigenous and Sámi research are combined with art history. With his art, Savio tried to show and prove to Norwegian politicians, the majority of the citizens and the Sámi people themselves that Sámi culture was strong and alive, and that it had the right to exist. Norway began its severe Norwegianisation policy in the late nineteenth and early twentieth centuries, part of a colonial policy and colonisation of the mind. Savio’s woodcuts were statements against this policy and were his attempts to decolonise the ugly stereotypes imposed on the Sámi.